(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2025)
Background. The molecular, supramolecular structure and physical-mechanical properties of composite materials obtained by dispersing the combined linear polyethylene and particulate silicon carbide, titanium and molybdenium exsentric vibrating mill. The correlation between the structure, hardness and heat resistance of composite materials. Methods. Co-dispersion of polyethylene and silicon, titanium, and molybdenum carbides allows changing the molecular and crystal structures of a typical thermoplastic polymer in the direction necessary to increase the physical and mechanical characteristics of composite materials. The maximum increase in hardness by 33 MPa and heat resistance by 31 K is observed when 7 vol.% SiC-d is introduced into the polymer. Results. The primary factor determining the increase in hardness and heat resistance of thermoplastic composites is the formation of chemical bonds between the components of the system: polymer macromolecules — highly dispersed carbides. Such bonds arise under the influence of mechanochemical effects during vibration grinding of carbide additives from PE and their introduction into the polymer melt. In connection with that, the crystallization of chemically grafted macromolecules is initiated at a higher temperature than in the original PE and ends with the formation of a more perfect crystalline structure of the polymer. At the same time, intermolecular crosslinks and a spatial network in PE are also formed. Conclusions. Such transformations in the structure of the crystallized thermoplastic are accompanied by an increase in the hardness and heat resistance of the composite materials.